Development of a field testing protocol for the biomechanical analysis of snowboard jump landings - a pilot study - McAlpine, P.; Kersting, U. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
A biomechanical analysis of snowboard jump landings is yet to be published. The purpose of this work was to develop a protocol to allow the collection of meaningful data in a real snowboarding environment. A video calibration technique was developed to provide superior measurement accuracy over a standard central cube calibration. The accuracy of a snowboard mounted force plate was assessed under various loading conditions. It was concluded that its performance was satisfactory and comparable to previous designs of a similar nature. Once the test protocol was finalised, data were collected from three experienced snowboarders performing jumps. The loads applied at the lead foot were found to be of high magnitude. Based on previous cadaver research, these high loads coupled with the kinematic data revealed a potential for ankle injury during snowboard landing events.